A partial mechanistic understanding of the North American monsoon. Issue 23 (4th December 2014) - Erfani, Ehsan; Mitchell, David
Abstract An understanding of the major governing processes of North American monsoon (NAM) is necessary to guide improvement in global and regional climate modeling of the NAM, as well as NAM's impacts on the summer circulation, precipitation, and drought over North America. A mechanistic understanding of the NAM is suggested by incorporating local‐ and synoptic‐scale processes. The local‐scale mechanism describes the effect of the temperature inversion over the Gulf of California (GC) on controlling low‐level moisture during the 2004 NAM. The strong low‐level inversion inhibits the exchange between the moist air in the marine boundary layer (MBL) and the overlying dry air. This inversion weakens with increasing sea surface temperatures (SSTs) in GC and generally disappears once SSTs exceed 29.5°C, allowing the moist air, trapped in the MBL, to mix with free tropospheric air. This leads to a deep, moist layer that can be transported by across‐gulf (along‐gulf) flow toward the NAM core region (southwestern U.S.) to form thunderstorms. On the synoptic scale, climatologies from 1983 to 2010 exhibit a temporal correspondence between coastal warm tropical surface water, NAM deep convection, NAM anticyclone center, and NAM‐induced strong descent. A hypothesis is proposed to explain this correspondence, based on limited soundings at the GC entrance (suggesting this local mechanism may also be active in that region), the climatologies, and the relevant literature. The warmest SSTs moving up the coast may initiate NAM convection and atmospheric heating, advancing the position of the anticyclone and the region of descent northward.